The Peripheral Hearing and Central Auditory Processing Skills of Individuals With Subjective Memory Complaints - Jayakody, Dona M. P.; Menegola, Holly K.; Yiannos, Jessica M.; Goodman-Simpson, Jack; Friedland, Peter L.; Taddei, Kevin; Laws, Simon M.; Weinborn, Michael; Martins, Ralph N.; Sohrabi, Hamid R. (Frontiers in Neuroscience, 2020)
Abstract Purpose: This study examined the central auditory processing (CAP) assessment results of adults between 45 and 85 years of age with probable pre-clinical Alzheimer's disease- i.e. individuals with subjective memory complaints (SMCs) as compared to those who were not reporting significant levels of memory complaints (non-SMCs). It was hypothesized that the SMC group would perform significantly poorer on tests of central auditory skills compared to participants with non-SMCs (control group). Methods: A total of 95 participants were recruited from the larger Western Australia Memory Study and were classified as SMCs (N = 61; 20 males and 41 females, mean age 71.47 + 7.18 years) and non-SMCs (N = 34; 10 males, 24 females, mean age 68.85 + 7.69 years). All participants completed a peripheral hearing assessment, a CAP assessment battery including Dichotic Digits, Duration Pattern Test, Dichotic Sentence Identification, Synthetic Sentence Identification with Ipsilateral Competing Message and the Quick-Speech-in-Noise, and a cognitive screening assessment. Results: The SMCs group performed significantly poorer than the control group on Synthetic Sentence Identification with Ipsilateral Competing Message -10 dB and -20 dB signal-to-noise conditions. No significant differences were found between the two groups on the peripheral hearing threshold measurements and other CAP assessments. Conclusions: The results suggest that individuals with SMCs perform poorly on specific CAP assessments in comparison to the controls. The poor CAP in SMC individuals may result in a higher cost to their finite pool of cognitive resources. The CAP results provide yet another biomarker that supports the hypothesis that SMCs may be a primary indication of neuropathological changes in the brain. Longitudinal follow up of individuals with SMCs, and decreased CAP abilities should inform whether this group is at higher risk of developing dementia as compared to non-SMCs and those SMC individuals without CAP difficulties. Key words: Hearing loss, central auditory processing, dementia, subjective memory complaints, APOE-e4